Elimination the redundancy in coverage of a topological object with rectangles - A. A. Butov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The approximate method of finding the shortest path of topological object covering by rectangles of type polygon given in discrete form by many nodal points is described. The discrete form of the description of the polygon eliminates topological design problem connected with the presence of problems of computational accuracy. The article refers to the next phase of the research related to the overall task of developing a software system for the preparation of topology information for microphotograph image generators.